PROYEKSI CAPAIAN AKHIR INDIKATOR MAKRO RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) 2021-2026 KABUPATEN SERANG - Ibrohim Abdul Halim; Rachmat Maulana; M. Robbi Qawi; Haryo Setyoko (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2025)
Serang Regency has a Regional Medium-Term Development Plan target that will end in 2026. This study attempts to determine whether the four macro-indicator targets in the Regional Medium-Term Development Plan (RPJMD) can be achieved as planned: the Human Development Index, Economic Growth Rate, Poverty Rate, and Unemployment Rate. This study aims to analyze the projected achievement of macroeconomic indicators in the 2021-2026 RPMJD in Serang Regency. Using the Exponential Trend Smoothing method to calculate indicator projections, the study found that the Human Development Index (HDI), the Economic Growth Rate (LPE), and the Unemployment Rate are projected to exceed the targets, while the Poverty Rate remains below the target set in the 2021-2026 RPJMD. The Serang Regency Government needs to prioritize the preparation of the next RPJMD to address poverty issues..